A bibliometric analysis of the application of physical therapy in knee osteoarthritis from 2013 to 2022 - Huang, Chenglan; Hou, Yutong; Yang, Yunxiao; Liu, Jiaqi; Li, Ya; Lu, Dezhi; Chen, Sha; Wang, Jinwu (Frontiers in Medicine, 2024)
Background: Knee osteoarthritis (KOA) is one of the most common chronic joint diseases. Physical therapy, a non-invasive approach, is extensively used in its treatment. Although bibliometrics is a reliable method to evaluate the significance and impact of research fields, systematic bibliometric analyses in this area are lacking. This study aims to perform a bibliometric analysis covering 2013 to 2022, to highlight the current state, key focuses, and trends in physical therapy for KOA.Methods: This study utilizes the Web of Science Core Collection to gather relevant literature on physical therapy and KOA from 2013 to 2022. CiteSpace and VOSviewer software facilitated the visual analysis of the annual publications, geographic and institutional distributions, journals, authors, references, and keywords in this field.The study analyzed 1,357 articles, showing an overall increase in publications over time from 71 countries and 2,302 institutions. The United States and Australia emerged as leaders in this field. The analysis identified 6,046 authors, with Kim L. Bennell as the most prolific and Bellamy N. receiving the most citations. BMC Musculoskeletal Disorders published the most articles, while Osteoarthritis and Cartilage received the most citations. High-impact articles were authored notably by McAlindon TE, Bannuru RR, Fernandes L, and Bennell KL. Keyword analysis highlighted a strong focus on patient self-management, exercise therapy, physical factor therapy, and remote rehabilitation.The bibliometric analysis confirms significant interest and ongoing research in physical therapy for KOA treatment from 2013 to 2022, indicating a growing field. Journals